ETHICS OF ISLAMIC EDUCATIONAL COMMUNICATION - Suyani, Erni; Usiono, Usiono (Universitas Dharmawangsa, 2024)
When ethics are combined with communication, then ethics become the foundation of communication, ethics provide a moral foundation in building morality towards all attitudes and behaviors of a person in communication. Thus, without ethics communication is unethical. Communication theory according to Islamic teachings is always bound to the commands and prohibitions of Allah SWT or the Qur'an and Sunnah of the Prophet Muhammad SAW. Basically, religion as a rule and as behavior is a message (information) to citizens to behave in accordance with God's commands and prohibitions. In other words, communication according to religious teachings greatly glorifies ethics which are accompanied by sanctions in the afterlife. The Qur'an also mentions communication as one of human nature. To find out how humans should communicate. The Qur'an provides keywords (key concepts) related to this. Communicators and communicants are required to speak softly, honestly, according to the facts, leave a mark on the heart, accurately and prioritize morals. When this concept is used by both parties, then appreciation and respect from both parties will be apparent and the effect will produce effective communication and in accordance with the teachings of Islam. This is based on the assumptions, namely: First; that Islamic educational communication has a different dimension from educational communication in general. Second; The Qur'an itself believes that there are core values and principles in educational communication that need and must be developed so that teachers can use them as a reference in learning. Where teachers as communicators and students as communicants must practice these ethics in communicating. The rules, principles, or ethics of Islamic communication are a form of success in the learning process, therefore ethics in educational communication in Islam are considered capable of bridging problems, especially moral education.